2017
DOI: 10.1038/cddis.2017.314
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate, a prototypic chemopreventative agent for protection against cisplatin-based ototoxicity

Abstract: Cisplatin-induced ototoxicity is one of the major factors limiting cisplatin chemotherapy. Ototoxicity results from damage to outer hair cells (OHCs) and other regions of the cochlea. At the cellular level, cisplatin increases reactive oxygen species (ROS) leading to cochlear inflammation and apoptosis. Thus, ideal otoprotective drugs should target oxidative stress and inflammatory mechanisms without interfering with cisplatin's chemotherapeutic efficacy. In this study, we show that epigallocatechin-3-gallate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 72 publications
4
103
0
Order By: Relevance
“…43 An extract from green tea epigallocatechin-3gallate (EGCG) was shown to protect against cisplatin ototoxicity in the rat and tumor-bearing mouse without interference with the tumor killing efficacy of cisplatin. 15 EGCG protected against cisplatin-induced hair cell damage, ABR threshold shifts, and prevented a decrease in the strial Na/K-ATPase activity. 15 Intratympanic application of siRNAs against TRPV1, NOX3, and STAT1 provided protection against cisplatin ototoxicity in rat model by decreasing ROS generation and preventing inflammation in the cochlea.…”
Section: Protective Agents-preclinical Studiesmentioning
confidence: 89%
See 2 more Smart Citations
“…43 An extract from green tea epigallocatechin-3gallate (EGCG) was shown to protect against cisplatin ototoxicity in the rat and tumor-bearing mouse without interference with the tumor killing efficacy of cisplatin. 15 EGCG protected against cisplatin-induced hair cell damage, ABR threshold shifts, and prevented a decrease in the strial Na/K-ATPase activity. 15 Intratympanic application of siRNAs against TRPV1, NOX3, and STAT1 provided protection against cisplatin ototoxicity in rat model by decreasing ROS generation and preventing inflammation in the cochlea.…”
Section: Protective Agents-preclinical Studiesmentioning
confidence: 89%
“…15 EGCG protected against cisplatin-induced hair cell damage, ABR threshold shifts, and prevented a decrease in the strial Na/K-ATPase activity. 15 Intratympanic application of siRNAs against TRPV1, NOX3, and STAT1 provided protection against cisplatin ototoxicity in rat model by decreasing ROS generation and preventing inflammation in the cochlea. 19 A novel compound was recently reported to ameliorate cisplatin ototoxicity in rodents.…”
Section: Protective Agents-preclinical Studiesmentioning
confidence: 89%
See 1 more Smart Citation
“…administered EGCG mitigated cisplatin-induced hearing loss along with a marked reduction in the loss of outer hair cells in the basal cochlear region. Importantly, chemotherapeutic drug-induced toxicity was also reduced mainly though suppression of apoptotic markers and oxidative stress [14] It has recently been reported that IFNγ-mediated PD-L1 levels were noted to be downregulated after treatment with green tea extracts and EGCG mainly through inhibition of JAK2/STAT1 signaling in A549 cells [15]. Likewise, EGF-stimulated PD-L1 upregulation was reduced in EGCG-treated Lu99 cells by inactivation of EGFR/AKT transduction cascade.…”
Section: Targeting Of Jak/stat Signalingmentioning
confidence: 92%
“…Orally administered EGCG mitigated cisplatin-induced hearing loss along with a marked reduction in the loss of outer hair cells in the basal cochlear region. Importantly, chemotherapeutic drug-induced toxicity was also reduced mainly though suppression of apoptotic markers and oxidative stress [14].…”
Section: Targeting Of Jak/stat Signalingmentioning
confidence: 99%